Development of a complex intervention to test the effectiveness of peer support in type 2 diabetes - O'Kelly Fergus; Whitford David; Smith Susan M; Paul Gillian; O'Dowd Tom (BMC, 2007)
Abstract Background Diabetes is a chronic illness which requires the individual to assume responsibility for their own care with the aim of maintaining glucose and blood pressure levels as close to normal as possible. Traditionally self management training for diabetes has been delivered in a didactic setting. In recent times alternatives to the traditional delivery of diabetes care have been investigated, for example, the concept of peer support which emphasises patient rather than professional domination. The aim of this paper is to describe the development of a complex intervention of peer support in type 2 diabetes for a randomised control trial in a primary care setting. Methods The Medical Research Council (MRC) framework for the development and evaluation of complex interventions for randomised control trials (RCT) was used as a theoretical guide to designing the intervention. The first three phases (Preclinical Phase, Phase 1, Phase 2) of this framework were examined in depth. The Preclinical Phase included a review of the literature relating to type 2 diabetes and peer support. In Phase 1 the theoretical background and qualitative data from 4 focus groups were combined to define the main components of the intervention. The preliminary intervention was conducted in Phase 2. This was a pilot study conducted in two general practices and amongst 24 patients and 4 peer supporters. Focus groups and semi structured interviews were conducted to collect additional qualitative data to inform the development of the intervention. Results The four components of the intervention were identified from the Preclinical Phase and Phase 1. They are: 1. Peer supporters; 2. Peer supporter training; 3. Retention and support for peer supporters; 4.Peer support meetings. The preliminary intervention was implemented in the Phase 2. Findings from this phase allowed further modeling of the intervention, to produce the definitive intervention. Conclusion The MRC framework was instrumental in the development of a robust intervention of peer support of type 2 diabetes in primary care. Trial registration Current Controlled Trials ISRCTN42541690